Clinical Findings Children Presenting with NonaAccidental Injuries to the Trauma Unit at the Red Cross War Memorial Childrenas Hospital (Global Journal of Medical Research, 2015)
This study intends to describe the patterns of Non Accidental Injury (NAI) in the population of children seen at Red Cross War Memorial Children's Hospital trauma unit. Child abuse is a serious problem worldwide and can be difficult to detect. Children who experience the consequences of abuse in most cases end up being treated at Emergency Centres. All children between the ages of 0 -13 years will be sampled by the use of selective selection. Trauma registers and ward registers will be used to identify children with suspected non-accidental injuries. The data will be analysed to show which types of non-accidental injuries were most prominent, what the causes were, where they happened, who the caregiver was and how long it took before presenting the child to hospital after infliction of such injury.
Keywords: non#x2013; accidental injury; childhood; burn; injuries; abuse; patients; cape town; western cape; south africa